Age and sexual variation of morphometric traits in Darevskia lindholmi, Szczerbak, 1962 (Sauria, Lacertidae, Darevskia) - Peskov, V.M.; Syniavska, I.O. (Збірник праць Зоологічного музею, 2016)
Based on results obtained by investigation of morphological differentiation of individuals of different age and sex, a highly correlated variation of 33 morphometric traits has been revealed in Lindholm’s rock lizard, Darevskia lindholmi (Szczerbak, 1962). It has been proved that the increase of linear body dimensions reflects the basic (ontogenetic) trend of variation of traits during late ontogenesis of D. lindholmi. It has been shown that sexual differences of some traits in D. lindholmi are almost absent, while by the linear body dimensions (the value of the first canonical root) males are larger than females. The age-related morphological differentiation of this lizards significantly exceeds sexual differences among adult individuals. По результатам исследования морфологической дифференциации особей разного возраста и пола выявлено высокий уровень коррелятивной изменчивости 33 морфометрических признаков у ящерицы Линдгольма. Доказано, что увеличение линейных размеров тела отражает основной (онтогенетический) тренд изменчивости признаков в позднем онтогенезе D. lindholmi. Показано, что половые различия по отдельным признакам у ящерицы Линдгольма практически отсутствуют, в то время как по линейным размерам тела (значение первой канонической переменной) самцы крупнее самок. Морфологическая дифференциация ящериц по возрасту значительно превышает половые различия между взрослыми ящерицами. За результатами дослідження морфологічної диференціації особин різного віку і статі виявлено високий рівень корелятивної мінливості 33 морфометричних ознак у ящірки Ліндгольма. Доведено, що збільшення лінійних розмірів тіла відображає основний (онтогенетичний) тренд мінливості ознак у пізньому онтогенезі D. lindholmi. Показано, що статеві відмінності за окремими ознаками у ящірки Ліндгольма практично відсутні, в той час як за лінійними розмірами тіла (значення першої канонічної змінної) самці крупніші за самок. Морфологічна диференціація ящірок за віком значно перевищує статеві відмінності між дорослими ящірками.